2021
DOI: 10.1108/hff-08-2021-0519
|View full text |Cite
|
Sign up to set email alerts
|

On the performance of RANS turbulence models in predicting static stall over airfoils at high Reynolds numbers

Abstract: Purpose This paper aims to conduct, a detailed investigation of various Reynolds averaged Navier–Stokes (RANS) models to study their performance in attached and separated flows. The turbulent flow over two airfoils, namely, National Advisory Committee for Aeronautics (NACA)-0012 and National Aeronautics and Space Administration (NASA) MS(1)-0317 with a static stall setup at a Reynolds number of 6 million, is chosen to investigate these models. The pre-stall and post-stall regions, which are in the range of ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…With the classic k - ∈ turbulence model and Reynolds stress model (RSM), a medium Re (360,000) case has been assessed by Almohammadi (2022) for up to 20° AoA. For high Re , Nived et al (2022) investigated fluid flow with Spalart–Allmaras (SA) model, Menter’s k - ω SST model, k - kL model and SA-Bas Çakmakçıoğlu modified (SA-BCM) transition model (Çakmakçıoğlu et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…With the classic k - ∈ turbulence model and Reynolds stress model (RSM), a medium Re (360,000) case has been assessed by Almohammadi (2022) for up to 20° AoA. For high Re , Nived et al (2022) investigated fluid flow with Spalart–Allmaras (SA) model, Menter’s k - ω SST model, k - kL model and SA-Bas Çakmakçıoğlu modified (SA-BCM) transition model (Çakmakçıoğlu et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Turbulent separation bubble starting from leading edge is predicted by 𝑘𝑘 − 𝜔𝜔 SST turbulence model at this angle of attack. From Figure 5 it can be observed that the flow stalls at 9-degree angle of attack and the performance of RANS based turbulence models in the pre and post stall regions are not reliable (25,26). Thus, the special flow separation behavior observed at these angles of attack need to be validated with experiments or LES/DNS simulations.…”
Section: Validation Of Transition 𝑘𝑘 − 𝜔𝜔 Sst Turbulence Modelmentioning
confidence: 99%
“…In another investigation, they analyzed the influence of this flow control on NACA 0025 at different Reynolds numbers (Khoshnevis et al, 2020). Some interesting results on this topic can be found in Gleize et al (2022), Nived et al (2022).…”
Section: Introductionmentioning
confidence: 99%